Distributed Control System With Aperiodic Sampled Time-Delayed Data for Batteries and Renewable Energy Sources in Microgrid - Zhang, Runfan; Hredzak, Branislav (IEEE transactions on sustainable energy, 2020)
This paper proposes an aperiodic sampled and time delayed data based distributed control system for frequency restoration, state of charge balancing and voltage restoration in a microgrid with distributed batteries and PV systems. Lyapunov-Krasovskii functionals and linear matrix inequalities are used to calculate the control system parameters and ensure its stability. The proposed control method is scalable since the stability depends only on the largest and smallest/second smallest eigenvalues of the communication graph Laplacian matrices. Real-time digital simulator is used to verify the proposed control method on an IEEE 13 node test feeder with variable loads.